Understanding and Satisfaction towards STEM Education of Primary School Teachers through Professional Development Program - Suebsing, S.; Nuangchalerm, P. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
The integration approach is not new to education, but it is very necessary for currently educating management. The study aims to explore the efficiency of STEM education for primary teachers through professional development. Participants were 200 primary school teachers who have been working for Roi Et Province, Thailand. STEM education manual guide for teacher, achievement test, and satisfaction questionnaire were used for research instruments. Experimental research, pre-test and posttest design were employed for data collection. The statistics used for data analysis were average, standard deviation, percentage and dependent t-test. Findings revealed that the efficiency of STEM education for primary school teachers reached criteria of 81.50/86.25. Primary teachers had understanding in STEM education by mean score of posttest was higher than pretest score at .01 level of statistical significantly differences. Also, they had satisfaction towards STEM Education at the highest level.